Massage for sport performance - McGilicuddy, Michael 1950- (Human Kinetics, 2011)
Perform at the highest level with "Massage for Sport Performance." This book and DVD demonstrate self-massage and partner massage for deep-tissue pain relief, injury rehabilitation, and speedy muscle recuperation. Optimal performance and quick relief are readily available with pre- and postevent massages, recovery massages, and spot treatments